The Determinant Factors on The Movement of Sharia stock in Indonesia - Amijaya, Rachmania Nurul Fitri; Sholikhin, Mohammad Yusron; Pratiwi, Azizah Esti (IJIBE (International Journal of Islamic Business Ethics), 2020)
This study aims to examine the determinant factors that influence Islamic stocks, JII. The development of the global economy will have an impact on economic turnover in Indonesia. This condition leads to sharing prices will be affected by the global economy. Strengthening in various sectors is needed so that JII stability can be maintained. This study uses quantitative methods with the Vector Error Correction Model (VECM) analysis which can determine the factors that influence the Jakarta Islamic Index (JII) in the long run. The time-series data used is monthly data from January 2011 to December 2018. The result of this research presents the macroeconomic variables affect JII in the long run. This has implications for JII stability depending on the exchange rate of the rupiah against the US dollar, the business cycle, inflation, economic growth, and interest rates. Exchange rates and business cycles have a negative relationship with JII. Meanwhile, interest rates, CPI and IPI have a positive relationship with JII. This research shows the macroeconomic factors from the business-cycle, which can be taken to be determined. It seems that this study might be a suggestion for investors in making wise decisions in investing. Furthermore, the government plays a very important role in maintaining the stability of Islamic stocks and the factors that influence them. In addition, strengthening monetary policy is needed due to the stock movements cannot be separated from the policy.